Meckel syndrome: what are the minimum diagnostic criteria?. Issue 6 (June 1994) - Wright, C; Healicon, R; English, C; Burn, J
Abstract : Two sibs are described, the first of whom presented the classic Meckel syndrome triad of encephalocele, postaxial polydactyly, and characteristic renal cystic changes. The second sib had none of these abnormalities, but did show urethral atresia and preaxial polydactyly, two features previously described in some patients with Meckel syndrome. The two cases illustrate both the wide phenotypic spectrum of Meckel syndrome and the difficulty of attempting to define minimum diagnostic criteria for the disorder. The clinical implications arising from this problem are discussed.